Oral health among children in the Barents region: study on determinants of child’s oral health, their oral related quality of life and quality of dental care - Koposova, Natalia V (University of Tromsø, 2013)
Papers 1 and 2 of this thesis are not available in Munin: 1. Natalia Koposova, Eeva Widström, Martin Eisemann, Roman Koposov, Harald M. Eriksen: 'Oral health and quality of life in Norwegian and Russian school children: A pilot study', Stomatologija, Baltic Dental and Maxillofacial Journal (2010), vol.12:10-16. Available at http://www.sbdmj.com/101/101-02.html 2. Natalia Koposova, Harald M Eriksen, Eeva Widström, Bjørn Helge Handegård, Mikhail Pastbin, Roman Koposov: 'Caries prevalence and determinants among 12-year-olds in North-West Russia and Northern Norway' (manuscript) In most industrialised countries, children’s and adolescents’ oral health has improved during the past 15 years. This is especially the case in the Nordic and Western European countries. The aim of the present series of studies was to assess the dental status, its determinants and oral health related quality of life in 12-year olds children from two regions in the Barents area, in Northern Norway and in North-West Russia. One study also analysed the oral health care provision systems and their performance in all countries in the Barents region. Four studies based on three data sets were undertaken. A pilot study comprising of questionnaires to 12-year olds children and their parents and a clinical examination of the children was undertaken in Severodvinsk (n=70) and in Tromsø (n=78) in 2009. A new clinical study, modified according to the findings of the pilot study, was conducted during 2010-2011 on 590 children in Arkhangelsk and 246 in Tromsø. Participants were selected using a stratified cluster sample procedure. Clinical examinations used methods recommended by the WHO. Both the children and their parents filled in questionnaires about determinants of dental caries and perceived oral health related quality of life of the children. The participation rate was 87% in Russia and 47% in Norway. Conventional statistical methods were used in the analyses. For the fourth study, the data were collected from national and local reports, ...